1999
DOI: 10.1002/clc.4960221308
|View full text |Cite
|
Sign up to set email alerts
|

Efficient in vivo catheter-based pericardial gene transfer mediated by adenoviral vectors

Abstract: Adenoviral vectors are promising agents for a number of in vivo gene therapy applications including diseases of the heart and coronary vessels. Efficient intravascular gene transfer to specific sites has been achieved in occluded vessels, but otherwise is hampered by the effect of blood flow on localized vector uptake in the vessel wall. An alternative delivery approach to coronary arteries is the expression of diffusible gene products into the pericardial space surrounding the heart and coronary arteries. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 36 publications
1
23
0
1
Order By: Relevance
“…This study confirms our initial description of the effectiveness of percutaneous instillation of material into a normal pericardial space with a helical needle-tipped catheter, 16,17 as well as by a transthoracic approach. 20 This method appears to be reasonably safe, with no evidence of adverse sequelae over several days after the procedure.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study confirms our initial description of the effectiveness of percutaneous instillation of material into a normal pericardial space with a helical needle-tipped catheter, 16,17 as well as by a transthoracic approach. 20 This method appears to be reasonably safe, with no evidence of adverse sequelae over several days after the procedure.…”
Section: Discussionsupporting
confidence: 86%
“…17 Briefly, a catheter inserted into the right jugular vein was advanced under fluoroscopic guidance into the right ventricle to the cardiac apex, then through the myocardium into the pericardial space. Proper catheter position was confirmed fluoroscopically by infusion of meglumine before flushing with 2 mL of saline.…”
Section: Biological Experimentsmentioning
confidence: 99%
“…10,11 Although some focal areas of the epicardium were reached after pretreatment with doxycyclin, 11 the pericardial approach does not yet seem to be sufficient to provide myocardial gene expression with homogeneous transmural distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Using imaging of luciferase light emission, March et al (1999) showed the feasibility of catheter-based pericardial local delivery of adenoviral vectors for gene therapy in dogs (159). One of the recombinant adenoviral expression vectors encoded luciferase in the cytoplasm.…”
Section: Imaging Luciferase Expression In Animalsmentioning
confidence: 99%